Site Selection Report of Farmer-led Participatory Maize Breeding Programme for the Middle Hills of Nepal - Subedi, M; Shrestha, P. (2000)
Maize is the second most important crop after rice in Nepal. Maize is grown largely on bari land during summer. The productivity of maize is quite low. A number of factors appear to be in play for the low productivity in the middle hills of Nepal.